1999
DOI: 10.1046/j.1439-0442.1999.00201.x
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility and Compatibility of Mixed Diets and Faecal Consistency in Different Breeds of Dog

Abstract: The digestive capacity of dogs varying in body size was tested. Digestive experiments were conducted with 10 different canine breeds (n = 66) with body weights ranging from 4.2 to 52.5 kg with 4-9 individuals. The animals were fed a canned or a dry commercial diet with a constant dry matter intake of 13 g/kg BW/day, except in Irish wolfhounds, which ingested only 10 g dry matter with the canned diet. Faecal dry matter was around 14% (absolutely) higher for the dry diet compared to the canned food, with a tende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 8 publications
5
49
0
2
Order By: Relevance
“…The propensity for large-breed dogs to produce poorquality feces is well known (Zentek and Meyer, 1995;Meyer et al, 1999;Weber et al, 2003b;Hernot, 2005). However, body size is not the only factor; some large dogs are particularly sensitive, whereas others are not.…”
Section: Effect Of Dog Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The propensity for large-breed dogs to produce poorquality feces is well known (Zentek and Meyer, 1995;Meyer et al, 1999;Weber et al, 2003b;Hernot, 2005). However, body size is not the only factor; some large dogs are particularly sensitive, whereas others are not.…”
Section: Effect Of Dog Sizementioning
confidence: 99%
“…Digestive tolerance can be assessed by determining fecal quality (consistency, moisture, volume, odor, and color), and several studies have shown that there is a wide range of digestive tolerance levels among dogs, especially related to body size, breed, or both (Meyer et al, 1999;Weber et al, 2002). Large-breed dogs are prone to producing feces of poor quality (Zentek and Meyer, 1995;Meyer et al, 1999), which are typically not well formed, contain more water, and seem to be diarrheal in some instances. Two main explanations have been proposed for this: reduced overall absorption of electrolytes, or greater fermenta-1 Supported by Royal Canin SA, Aimargues, France.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important consideration in light 258 of the work of Sartor et al [32] who showed the portal blood flow 259 volume (mL/min/kg) is inversely related to body weight. Therefore, [38]. These investigators observed that as body 402 weight increased, there was a trend toward an increase in total 403 fecal water content but a decrease in the percent of unbound fecal 404 water (Fig.…”
mentioning
confidence: 93%
“…Based upon published information, this review 33 addresses breed differences in gastrointestinal (GI) physiology and discusses the in vivo implications of 34 these differences. In addition to the importance of such information for understanding the variability that 35 may exist in the performance of oral dosage forms in dogs for the purpose of developing canine therapeu- 36 tics, an appreciation of breed differences in GI physiology can improve our performance prediction of oral 37 drug formulation performance when we extrapolate bioavailability results from the dog to the humans, 38 and vice versa. In this literature review, we examine reports of breed associated diversity in GI anatomy 39 and morphology, gastric emptying time (GET), oro-cecal transit time (OCTT), small intestinal transit time 40 (SITT), large intestinal transit time (LITT), intestinal permeability, sodium/potassium fecal concentrations, 41 intestinal flora, and fecal moisture content.…”
mentioning
confidence: 99%
“…A qualidade de um alimento comercial esta diretamente relacionada com o volume e a consistência fecal que ele "causa" (MEYER et al 1999).…”
Section: Escore E Volume Fecalunclassified